BE THE CHANGE YOU WANT TO SEE IN THE WORLD- THE CARVING OF SOCIAL RESPONSIBILITY AMONG THE UNIVERSITY STUDENTS - Mathew, Ancy; Basavaraja, B M (International Journal of Research -GRANTHAALAYAH, 2018)
This paper focuses on integrating social responsibilities among its stake holders who are key persons involved in the operations of the university. Required challenges such as global warming, climate change, shortage of water, lack of good infrastructure, food safety and lack of renewable energy sources to lead a dignified human life. Universities play greater role in shaping the future citizens of the globe. Implementation of CSR programs enhances benefits to the share holders and stake holders. CSR influences the ethical validity and enhances reputation among the education vendors. Students active participation in CSR activities provides self-awareness, development, ethics and values. These activities enhances teamwork, event management, networking and interpersonal skills. This paper is focused on a real life journey of CSR practices in a private, comprehensive technical university of south India. It also demonstrates how a higher education institution can take up and get embedded CSR in the university system in tune with vision of the University.